Exploring the Pharmacology of Ginkgo biloba: A Solution for Cardioavascular Disease - Azhari, Nabilah Syahirah; Abdila, Alya Nur; Br Barus, Sari Apriani; Silitonga, Melva (Florea : Jurnal Biologi dan Pembelajarannya, 2025)
Cardiovascular diseases are a leading cause of global mortality, necessitating the exploration of safe and effective treatments. Ginkgo biloba, an ancient medicinal plant, has gained attention for its potential in managing cardiovascular health. This review explores the pharmacological mechanisms of Ginkgo biloba, focusing on its cardiovascular benefits. This review aims to understand the pharmacological mechanisms of Ginkgo biloba in addressing cardiovascular diseases. The method used in this review was a systematic review conducted through the PRISMA guidelines. Ginkgo biloba contains bioactive compounds, including flavonoids, terpenoids, and polysaccharides, that exhibit anti-diabetic, anti-inflammatory, anti-fatty liver hemorrhagic syndrome, anti-oxidant, anti-depressant, and anti-cancer. In conclusion, Ginkgo biloba offers a promising therapeutic solution for cardiovascular desease.